1995
DOI: 10.1002/art.1780380918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tenidap on canine experimental osteoarthritis i. morphologic and metalloprotease analysis

Abstract: Objective. To examine the effects of tenidap and diclofenac on osteoarthritic lesions and metalloprotease activity in experimental osteoarthritis (OA).Methods. The anterior cruciate ligament of the right stifle joint of 25 mongrel dogs was sectioned by a stab wound. Seven dogs received no treatment, 6 were treated with oral omeprazole (20 mg/day), another 6 were treated with diclofenac (0.25 mg/kg/twice daily) plus omeprazole (20 mg/day), and 6 received oral tenidap (3 mg/kg/twice daily) plus omeprazole (20 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
87
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 61 publications
(101 citation statements)
references
References 48 publications
13
87
1
Order By: Relevance
“…Lesional joint cartilage in the placebo-treated group exhibited morphologic changes, including cartilage fibrillation and fissures, changes in cellularity, such as cloning and hypocellularity, and loss of Safranin O staining, as previously described (11,20,21) (Figure 2). A decrease in the histologic score of the medial femoral condyles, indicative of a reduced severity of the lesions, was observed in dogs with OA treated with pioglitazone (median histologic score 6.25 [range [3][4][5][6][7][8][9][10][11][12] in the placebo group versus 4.25 [range [3][4][5][6][7] in the 15 mg/day pioglitazone group and 5.5 [range [5][6] in the 30 mg/day pioglitazone group); this difference was sig- nificant following a dosage of 15 mg/day pioglitazone as compared with the placebo group (P Ͻ 0.05).…”
Section: Characteristics Of the Experimental Animalssupporting
confidence: 76%
See 4 more Smart Citations
“…Lesional joint cartilage in the placebo-treated group exhibited morphologic changes, including cartilage fibrillation and fissures, changes in cellularity, such as cloning and hypocellularity, and loss of Safranin O staining, as previously described (11,20,21) (Figure 2). A decrease in the histologic score of the medial femoral condyles, indicative of a reduced severity of the lesions, was observed in dogs with OA treated with pioglitazone (median histologic score 6.25 [range [3][4][5][6][7][8][9][10][11][12] in the placebo group versus 4.25 [range [3][4][5][6][7] in the 15 mg/day pioglitazone group and 5.5 [range [5][6] in the 30 mg/day pioglitazone group); this difference was sig- nificant following a dosage of 15 mg/day pioglitazone as compared with the placebo group (P Ͻ 0.05).…”
Section: Characteristics Of the Experimental Animalssupporting
confidence: 76%
“…At this time, it is not known whether the data obtained from animal model experimentation can be extrapolated to clinical observations. The experimental dog model of ACLT-induced OA has been used extensively for such purposes (20,21,23,(25)(26)(27) and could thus be an exception and serve as a useful tool in the study of human OA. Studies have recently shown that the positive effects of doxycycline on OA structural changes in an experimental dog model of OA (28) could also be seen in patients with knee OA treated with this drug (29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations